2020
DOI: 10.21037/tau.2020.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase type 5 inhibitor therapy provides sustained relief of symptoms among patients with chronic pelvic pain syndrome

Abstract: Background: Chronic prostatitis/chronic pelvic pain syndrome type III (CP/CPPS) is associated with pelvic pain, sexual dysfunction and irritative voiding. Sustained symptom relief has proven difficult with alpha blockers, antibiotics, and nonsteroidal anti-inflammatory drugs (NSAIDs). Phosphodiesterase type 5 (PDE5) inhibitors (PDE5is) have the potential to alleviate bladder urgency, relax the pelvic floor, and correct underlying erectile dysfunction; however, few studies have investigated the application of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Clinically, there are few studies discussing its role in CP/CPPS. Unfortunately, most of these studies either lacked control arm or run in BPH associated CP/CPPS or in combination with other medications [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinically, there are few studies discussing its role in CP/CPPS. Unfortunately, most of these studies either lacked control arm or run in BPH associated CP/CPPS or in combination with other medications [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In Pineault et al study, 25 patients (mean age 44.4 ± 12.9 years) were treated with tadalafil 5 mg daily for a mean duration of 1.3 ± 1.6 years. Although lacked control arm, they concluded that daily use of tadalafil for long time was associated with significant decreases in CPSI total, pain, urinary symptom and quality of life scores (− 12.8 ± 9.5, − 6.1 ± 4.1, − 2.4 ± 2.1 and − 4.5 ± 3.9, respectively) [21] The significant changes in CPSI scores, compared to baseline, in our study are found to be in accordance with the previously mentioned reports but with much limited changes. That limited changes of CPSI may be explained as our study included younger ages with longer duration of moderate/severe complaint or may be attributed to shorter study duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12.1.8 PDE5i : See 7.4. PDE5i may alleviate Cp/CPPS symptoms by reducing oxidative stress and inflammation on the prostate and PF 105 . (NEW)…”
Section: Section 12: Treatments For Cp/cpps and Related Sexual Dysfun...mentioning
confidence: 99%